Transformasi Moda Produksi Peternakan Sapi Perah di Kecamatan Cilengkrang Kabupaten Bandung - Abdullah, Nyimas Gisella Tiatira; Mauludin, Mochamad Ali; Sulistyati, Marina (Universitas Galuh, 2025)
The mode of production refers to the societal means and relations of organizing economic activity. It comprises force of production that influence productivity and relation of production that shape social structures. Cilengkrang Subdistrict, Bandung Regency, emerged as a dairy cattle farming center due to dairy cattle credit assistance from KUD Sinar Jaya. This study using a qualitative case study approach, analyzes the transformation of production modes in this region. Results indicate three distinct periods: the early pioneer (1980-2000), crisis and transition (2001-2010), and revival and diversification (2011-present). The study reveals shifts towards semi-petty commodity and petty commodity modes. Productive forces, primarily dairy cattle and land, varied across periods in terms of quantity. Production relations evolved from egalitarian to hierarchical with the introduction of hired labor.